Design of Quranic Learning Based on Herbartian Method: A Case Study in Educational Institutions in Indonesia - Wafa, Ali (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2024)
Quranic education plays a central role in shaping the Islamic character of students, but traditional approaches often fail to integrate values and critical understanding. This study aims to design Quranic learning based on the Herbartian method, known for its systematic and holistic instructional structure. The research employs library research methodology, with data derived from primary and secondary literature on the Herbartian method and Islamic education. The findings indicate that the application of the Herbartian method, consisting of five stages (preparation, presentation, association, generalization, and application), enables the integration of Quranic values into a systematic and applicable learning process. Implementation in Islamic educational institutions in Indonesia demonstrates improved comprehension, active participation, and the internalization of Quranic values by students. However, challenges such as limited teaching time and teacher competence need to be addressed through training and curriculum adjustments. This study implies the development of a more structured Quranic learning model that aligns with modern educational challenges while strengthening the integration of Western educational theories with Islamic values. The originality of this research lies in adapting the Herbartian method within the context of Islamic education, an area rarely explored, and its contribution to value-based Quranic learning.